2019
DOI: 10.1029/2018jd029317
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Laboratory Measurement of the O2 Collision‐Induced Absorption Band Near 1.27 μm

Abstract: The atmospheric band of O2 near 1.27 μm plays an important role in determining the air mass from ground or spaceborne atmospheric spectra. This band consists of narrow absorption lines of the anormalΔ1g−XnormalΣnormalg−3()0−00.25emtransitions superimposed to a much broader collision‐induced absorption (CIA) structure. Very accurate CIA binary coefficients, BO2−O2, BO2−N2, and BO2−air, are determined by highly sensitive cavity ring down spectroscopy from low density spectra (0.36 to 0.85 amagat) of pure oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
39
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 42 publications
(69 reference statements)
8
39
1
Order By: Relevance
“…The latter corresponds to the recent data measured by Mondelain et al [15] for values at room temperature. Their (small) temperature dependences were taken from Maté et al [12] using:…”
Section: Calculation Proceduressupporting
confidence: 91%
See 1 more Smart Citation
“…The latter corresponds to the recent data measured by Mondelain et al [15] for values at room temperature. Their (small) temperature dependences were taken from Maté et al [12] using:…”
Section: Calculation Proceduressupporting
confidence: 91%
“…Room temperature CIA binary coefficients were recently determined with improved accuracy, from low density spectra [i.e. from (0.97 to 2.3)10 19 molecule/cm -3 equivalent to 0.36 to 0.85 amagat] of pure oxygen and of an O2/N2 mixture by highly sensitive cavity ring-down spectroscopy (CRDS) [15]. Despite the lower sample pressures used in this CRDS study, the retrieved CIA coefficients were found in very good agreement with the FTS values by Maté et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, highly sensitive cavity ring down spectroscopy (CRDS) was used to determine the room temperature CIA binary coefficients from low density spectra (0.36 to 0.85 amagat) of pure oxygen and an O 2 /N 2 mixture at room temperature, over the wide 7513-8466 cm -1 region [10]. As concerned the study of the absorption lines, a first contribution was dedicated to low pressure spectra of pure O 2 in the 7920-8085 cm -1 interval for pressures up to 150 Torr [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since lines are quite isolated (see Fig. 1), a spectral range of about 1 to 2 cm -1 was considered at a time, in order to simplify the fitting procedure and to minimize the influence of the contribution of the CIA [10]. The contribution of lines close to the considered spectral region ( cm -1 from the center of the considered line) was nevertheless taken into account ± 1 using HITRAN2016 and fixed in the fitting procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation